WORKING CONDITIONS AND COMMON MENTAL DISORDERS IN TECHNICAL ADMINISTRATIVE SERVERS OF THE STATE UNIVERSITY OF FEIRA DE SANTANA IN THE COVID-19 PANDEMIC - Leão dos Santos, Edson (2023)
Currently, inadequate working conditions are increasingly present in people's lives, especially in the public investigated in this research, namely the technical-administrative workers of the Universidade Estadual de Feira de Santana (UEFS), which can negatively affect the physical and mental health of this public. The study aimed to analyze the association between working conditions and the prevalence of Common Mental Disorders (CMD) in technical-administrative servers at UEFS during the COVID-19 pandemic. This is a cross-sectional epidemiological study, carried out remotely, whose data collection tools were a sociodemographic questionnaire, questions about working conditions in home office and the Self-Report Questionnaire - 20 (SRQ - 20). The data showed that, from the 143 servers that comprised the sample, 55.2% manifested CMD; furthermore, a statistically significant association was observed between the occurrence of CMD and the variables sex, age and education, and remote working conditions. Therefore, it becomes evident the need for the institution to implement internal policies aimed at promoting improvements in the working conditions of these servers to reduce/amend the work-related CMD, improving their quality of life.